Associations between contraceptive use, physical activity, depression, and quality of life among women of childbearing age in Akure South Local Government area of Ondo State, Nigeria - Alimi, Olabisi Ganiyat (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Background: Population experts and policymakers are concerned about Nigeria's rapid annual population growth due to the country's high birth rate which was 5.3 births per woman in 2018. Fear of the side effects of modern contraceptives among Nigerian women contributes to the low rate of contraceptive use, which was reported to be 17% and 37% among married and sexually active unmarried women, respectively. Which is a significant cause of the high birth rate. Although the side effects of modern contraceptives on women's clinical and physiological variables are well known, studies examining the associations between contraceptive use and physical and psychosocial variables such as physical activity (PA), depression, and quality of life (QoL) in non-athletic Nigerian women of reproductive age are scarce. This study aimed to examine the associations between contraceptive use, PA, depression, and QoL among non-athletic women of childbearing age in Akure South Local Government, Ondo State, Nigeria. Methods: In a descriptive cross-sectional study, 646 women of childbearing age were recruited using the multistage sampling technique. The data of 496 current contraceptive users and 146 non-users were analysed, as 4 respondents did not respond regarding current contraceptive use status. The Global PA Questionnaire (GPAQ), Beck's Depression Inventory (BDI) and World Health QoL Organization Quality of Life Brief (WHOQoL BREF) were used to assess respondents' scores/levels of PA, depression and health-related quality of life (HRQoL). The GPAQ, BDI, and WHOQOL scores were compared between contraceptive users and non-users using non-parametric Quade Analysis of Covariance while age, married status, tribe, religion, and occupation were included covariates. PA, sedentary behaviour (SB), and BDI scores were categorized using guidelines. Contraceptive use/practice was the outcome variable. Pearson's chi-square test bivariate analysis and a multivariate logistic model were used to identify factors associated with contraceptive use (users and non-users). Crude and adjusted odds ratios and their confidence intervals were calculated to determine the significance of the association. The regression model was adjusted for age, marital status, religion, tribe, highest education level, occupation, awareness of contraceptives, current use, lifetime use, type, class, and duration of current contraception. "Statistical significance was set at p < 0.05. Results: The mean age of the respondents was 29.73Â±6.10 years. The contraceptive users and non-users were not significantly different regarding their ages (p = 0.135), marital status (p = 0.245), highest education (p = 0.444), occupation (p = 0.238), and tribe (p = 0.192). The respondents' lifetime and point prevalence of contraceptive uptake was 93.6% and 77.3%, respectively, while 72 (12.8%) reported experiencing contraception-related side effects. Of the 496 respondents who currently practice contraception, 146 (29.4%) were hormonal contraceptive users. The majority of the respondents had moderate and mild levels of PA (48.5%) and depression (51.4%), respectively, and a significantly higher proportion of contraceptive users had minimal and moderate depression levels than the non-users (p = 0.018). The contraceptive users demonstrated significantly higher median scores of BDI (p = 0.02), Physical health QoL (p < 0.001), environment QoL (p = 0.033) and overall QoL (0.004) than the non-users. Hormonal contraceptive users had significantly higher median PA walking/bicycling scores than non-hormonal users (p = 0.014). Respondents with mild and moderate depression levels had higher odds of being contraceptive users than those with minimal depression (AOR = 3.12, 95% CI = 1.43 "“ 6.80, p = 0.04 and 4.67, 95% CI = 1.92 "“ 11.36, p = 0.001 respectively). Conclusion: Contraceptive use is negatively associated with depression but positively related to Physical health, environment and overall domains of HRQoL. Healthcare professionals should consider women's mental and emotional condition while advising on family planning for optimal HRQoL.
Keywords: Exercise for women -- Nigeria -- Ondo State; Depression in women -- Nigeria -- Ondo State; Well-being -- Nigeria -- Ondo State; Quality of life -- Nigeria -- Ondo State; Contraception -- Side effects